The factors affecting the proliferation of mould fungi and mycotoxin production during the storage of wheat and the identification methods of the appearing branches - Nyéki, Ágnes; Peles, Ferenc Árpád; Mile, Irma Győriné (Acta Agraria Debreceniensis, 2012)
Nowadays, it is often suggested that, we should eat products made with whole grain cereals, despite of the fact that it raises the risk of consuming wheat products infected by mold and their toxins originated from the plough-lands and the stocks. Two third of the cultivated fields in Hungary are planted with cereals. The most alarming problem for food and feed security is caused by the Fusarium species. The greatest problem of all is caused by the mycotoxins. When they get into the food chain they can be a serious threat to public health. In addition, we have to face up to the problem of the effects of global warming that influence the growth of microbial infections in different ways. In this article we tried to summarize the effect of climate change on molds, the factors which have effect on growing and mycotoxin producing of molds and the identification methods of molds.